Challenges in Cybersecurity and Privacy - the European Research Landscape. - Bernabe, Jorge Bernal. (River Publishers, 2019)
This book introduces several cybersecurity and privacy research challenges and how they are being addressed in the scope of 15 European research projects.Each chapter is dedicated to a different funded European Research project, which aims to cope with digital security and privacy aspects, risks, threats and cybersecurity issues.